Pandemi Covid 19: Pelatihan Pajak bagi UMKM - Amelia Sandra; Rizka Indri Arfiant; Prima Apriwenni; Hanif Hanif (President University, 2020)
The Covid-19 Pandemic has made economic conditions in Indonesia, including MSME players,seriously worsened. The government has made many policies to ease the burden on MSMEs, one ofwhich is providing incentives in the field of taxation. There are still many MSME players who do nottake advantage of the incentives provided. The obstacles they face are the lack of socialization andtheir ignorance of using these facilities. For this reason, the community service team of Institut Bisnisdan Informatika Kwik Kian Gie collaborates with the OperBisnis organization to assist in introducingsimple accounting and utilizing tax incentives for MSMEs during the Covid-19 pandemic. The targetsin this activity are MSME entrepreneurs assisted by the non-profit organization OperBisnis, whofoster more than 50 UMKM entrepreneurs spread across Jabodetabek, Bandung, and Medan. Thesolution for MSMEs that have not done bookkeeping is expected to use a single entry system byrecording cash receipts and payments so that they can take advantage of government tax incentives.